Modified binder as well as preparation method and application thereof
By using the core layer, middle shell layer and outer shell layer structure of the modified adhesive in the negative electrode sheet of the lithium-ion battery, the problems of adhesive brittleness and floatation are solved, and the bonding performance and battery performance of the negative electrode sheet are improved.
Patent Information
- Application Number
- CN202411376091.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-31
AI Technical Summary
The existing lithium-ion battery negative electrode sheet adhesives have problems such as high brittleness, easy to lose powder, hard brittleness and cracking, and small particle size and easy to float, which affects the bonding performance between the coating and the negative electrode foil.
Design a modified adhesive, adopting the SBR core-shell structure of the inner core layer, the middle shell layer and the outer shell layer. The inner core layer and the middle shell layer are formed of styrene butadiene rubber, and the outer shell layer is connected by unsaturated acid and unsaturated ether substances. The monomer mass ratio and reaction conditions are optimized to form a modified binder with high strength and high toughness.
Effectively improve the problems of coating cracking and floating, improve the peeling force and bonding properties of the negative electrode sheet, promote the dispersion of active substances and conductive agents, and improve the energy density and circulation performance of the battery.
Smart Images

Figure CN119220208A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of binders, and in particular to a modified binder, a method for preparing the modified binder, a negative electrode sheet, a method for preparing the negative electrode sheet, and a lithium-ion battery. Background Art
[0002] As a clean and convenient energy source, lithium-ion batteries play a very important role in people's daily lives. More and more electrical devices need to use lithium-ion batteries to power them.
[0003] The main structure of lithium-ion batteries includes negative electrode sheets, positive electrode sheets, separators and electrolytes. In the manufacturing process of positive and negative electrode sheets, although the binder is an inactive component in the sheet, it is one of the important materials that must be used. Its main function is to ensure that the active material particles and the active particles and the current collector have a certain bonding strength during the use of the battery, forming a stable electrode structure, ensuring the integrity of the electrode during the charge and discharge process, and improving the conductivity and mechanical strength of the electrode.
[0004] Currently, the widely used lithium-ion battery binders mainly include oily binders such as polyvinylidene fluoride (PVDF), and water-based binders such as styrene-butadiene rubber (SBR) emulsion, carboxymethyl cellulose (CMC), and polyacrylic acid (PAA). Among the water-based binders commonly used for negative electrode plates, CMC has stable viscosity and good compatibility with other materials, and can provide stable viscosity and adhesion, but it is very brittle and the plate will lose powder severely after rolling or compacting; PAA material is hard and brittle, which can easily cause the plate to crack; SBR emulsion particles are small in size and easily float, which affects the bonding performance between the coating and the negative electrode foil.
[0005] Therefore, a high-strength, tough, and anti-floating binder is designed and developed so that it can meet the processing and application performance requirements of the negative electrode sheet when used in the negative electrode sheet. Summary of the invention
[0006] In order to solve or partially solve the problems existing in the related art, the present application provides a modified binder, a method for preparing a modified binder, a negative electrode sheet, a method for preparing a negative electrode sheet and a lithium ion battery, which can effectively improve the problems of cracking during negative electrode coating and floating of materials during coating, improve the peeling force of the negative electrode sheet, and have good bonding performance; and can improve and promote the dispersion of negative electrode active materials and conductive agents, increase the loading amount of negative electrode active materials, and improve battery energy density and cycle performance.
[0007] The first aspect of the present application provides a modified adhesive, which includes an inner core layer, a middle shell layer and an outer shell layer arranged in sequence from the inside to the outside; wherein the inner core layer and the middle shell layer are formed of styrene-butadiene rubber, and the strength of the inner core layer is greater than the strength of the middle shell layer; the outer shell layer is formed by unsaturated acid and unsaturated ether substances.
[0008] In some embodiments, the monomers of the inner core layer and the middle shell layer are both butadiene and styrene.
[0009] In some embodiments, the mass ratio of butadiene to styrene in the inner core layer is (20-40): (60-80), and the mass ratio of butadiene to styrene in the middle shell layer is (65-75): (25-35).
[0010] In some embodiments, the unsaturated acid is selected from at least one of acrylic acid, itaconic acid and maleic acid.
[0011] In some embodiments, the unsaturated ether is selected from at least one of propenyl phenyl ether, allyl methyl ether, allyl butyl ether and butyl vinyl ether.
[0012] In some embodiments, the content of unsaturated acid in the outer shell layer is ≤10 wt %.
[0013] In some embodiments, the content of the unsaturated ether in the outer shell layer is 1 wt% to 25 wt%, preferably 3 wt% to 20 wt%.
[0014] In some embodiments, in the outer shell layer, the mass ratio of the unsaturated acid to the unsaturated ether is (4-10):(3-18).
[0015] In some embodiments, in the modified binder, the monomer mass ratio of the inner core layer, the middle shell layer and the outer shell layer is (20-65): (20-65): (10-35).
[0016] The second aspect of the present application provides a method for preparing a modified binder, which comprises the following steps: 1) Mix butadiene and styrene in a certain mass ratio, add an initiator to react, and obtain a seed emulsion; 2) adding butadiene and styrene in a certain mass ratio to the seed emulsion, and adding an initiator to react to obtain a core-shell structured SBR polymer emulsion; 3) adding a certain mass ratio of unsaturated acid and unsaturated ether substances to the core-shell structured SBR polymer emulsion, mixing, and adding an initiator to react, to obtain an aqueous binder emulsion containing the modified binder as described in the first aspect of the present application.
[0017] In some embodiments, in the aqueous binder emulsion, the solid content of the modified binder is 25 wt% to 35 wt%, the viscosity is 500 cps to 1500 cps, and the particle size D50 is ≤1 μm.
[0018] In some embodiments, the reaction conditions of step 1) include: temperature of 3°C to 25°C, pressure of 3 MPa to 15 MPa, and reaction time of 2h to 5h; preferably 5°C to 10°C, 5 MPa to 10 MPa.
[0019] In some embodiments, the reaction conditions of step 2) include: temperature of 3°C to 25°C, pressure of 3 MPa to 15 MPa, and reaction time of 5h to 8h; preferably 5°C to 15°C, 5 MPa to 10 MPa.
[0020] In some embodiments, the reaction conditions of step 3) include: temperature of 3°C to 25°C, pressure of 1 MPa to 15 MPa, and reaction time of 3h to 5h; preferably 10°C to 15°C, 3 MPa to 8MPa.
[0021] The third aspect of the present application provides a negative electrode plate, which includes a negative electrode collector and a negative electrode active layer formed by coating a negative electrode slurry on the surface of the negative electrode collector; wherein the negative electrode slurry contains a negative electrode active material, and the modified binder as described in the first aspect of the present application or an aqueous binder emulsion prepared by the preparation method as described in the second aspect of the present application.
[0022] In some embodiments, the negative electrode active material includes graphite and a silicon-carbon composite.
[0023] In some embodiments, the silicon-carbon composite accounts for 1 wt% to 30 wt% of the negative electrode plate, preferably 5 wt% to 16 wt%.
[0024] In some embodiments, the modified binder accounts for 1.4 wt% to 2 wt% of the negative electrode sheet; preferably 1.6 wt% to 1.8 wt%.
[0025] In some embodiments, the negative electrode slurry has a solid content of 46 wt % to 54 wt % and a viscosity of 4000 cps to 7000 cps.
[0026] A fourth aspect of the present application provides a method for preparing a negative electrode sheet, which comprises the following steps: I) mixing carboxymethyl cellulose with a conductive agent to obtain a conductive adhesive; II) mixing the conductive glue and the negative electrode active material, and then adding the modified binder as described in the first aspect of the present application to obtain a negative electrode slurry; III) coating the negative electrode slurry on the negative electrode current collector, and drying to obtain the negative electrode sheet as described in the third aspect of the present application.
[0027] In some embodiments, in step II), the conductive glue is added to the negative electrode active material step by step to make the negative electrode active material evenly dispersed.
[0028] The fifth aspect of the present application provides a lithium-ion battery, comprising the negative electrode sheet as described in the third aspect of the present application, or the negative electrode sheet prepared by the preparation method as described in the fourth aspect of the present application.
[0029] The sixth aspect of the present application provides an electrical device or various energy storage systems using batteries as energy storage elements, which include the lithium-ion battery described in the fifth aspect of the present application.
[0030] The technical solution provided by this application may have the following beneficial effects: Through the SBR core-shell structure with an inner core layer, a middle shell layer and an outer shell layer, and the design of a binder with different strengths of the inner and outer layers, as well as the solvated chain segments formed by grafting unsaturated acids and unsaturated ether substances on the outer layer of the SBR core-shell structure, not only can the modified binder have the characteristics of high strength and high toughness, effectively improving the problem of coating cracking, but the modified binder can also be anchored on the surface of particles such as negative electrode active materials and conductive agents, promote the dispersion and suspension stability of various particles in the aqueous slurry, reduce and inhibit the floating problem of the SBR core-shell structure binder, improve the peeling force, and improve the bonding performance between the binder and other materials.
[0031] Through the application of the above-mentioned SBR core-shell structure binder in the negative electrode plate, the binder has high strength and high toughness, and can reduce the amount of binder used on the basis of meeting the bonding performance of the negative electrode material, meet and broaden the processing window of the negative electrode, thereby increasing the loading amount of the negative electrode main materials such as negative electrode active substances, conductive agents, etc., reducing battery impedance, and improving battery energy density and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail the exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0033] Figure 1 It is a schematic diagram of the structure of the modified binder prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0034] To make the present invention easy to understand, the present invention will be described in detail below. However, before describing the present invention in detail, it should be understood that the present invention is not limited to the specific embodiments described. It should also be understood that the terms used herein are only for describing specific embodiments and are not intended to be limiting.
[0035] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0036] Where a numerical range is provided, it is to be understood that each intermediate value between the upper and lower limits of the range and any other provisions or intermediate values in the specified range is encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges and are also encompassed within the present invention, subject to any explicitly excluded limits in the specified range. Where a specified range includes one or two limits, the scope excluding any or both of those included limits is also encompassed within the present invention. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically limited.
[0037] Unless otherwise defined, all terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials or equivalent methods and materials described herein can also be used in the practice or testing of the present invention, preferred methods and materials are now described.
[0038] Currently, the widely used lithium-ion battery binders mainly include oily binders such as polyvinylidene fluoride (PVDF), and water-based binders such as styrene-butadiene rubber (SBR) emulsion, carboxymethyl cellulose (CMC), and polyacrylic acid (PAA). Among the commonly used water-based binders for negative electrode plates, CMC has stable viscosity and good compatibility with other materials, and can provide stable viscosity and adhesion, but it is very brittle, and the plate will lose powder seriously after rolling or compacting; PAA material is hard and brittle, which can easily cause the plate to crack; SBR emulsion particles are small in size and easy to float, affecting the bonding performance between the coating and the negative electrode foil.
[0039] In response to the above problems, the embodiments of the present application provide a modified binder, a method for preparing a modified binder, a negative electrode sheet, a method for preparing a negative electrode sheet, and a lithium-ion battery, which can effectively improve the problems of cracking during negative electrode coating and material floating during coating, improve the peeling force of the negative electrode sheet, and have good bonding performance; and can improve and promote the dispersion of negative electrode active materials and conductive agents, increase the loading amount of negative electrode active materials, and improve battery energy density and cycle performance.
[0040] The modified binder involved in the embodiment of the present application includes an inner core layer, a middle shell layer and an outer shell layer arranged in sequence from the inside to the outside; wherein the inner core layer and the middle shell layer are formed of styrene-butadiene rubber, and the strength of the inner core layer is greater than that of the middle shell layer; the outer shell layer is formed by unsaturated acid and unsaturated ether substances. On the one hand, the SBR modified binder with a core-shell structure composed of an inner core layer, a middle shell layer and an outer shell layer, and the design of different strengths of the inner and outer layers, is endowed with the characteristics of both high strength and high toughness, which can effectively improve the problem of coating cracking; on the other hand, the hydrophilic functional group carboxyl and ether bond with bonding properties introduced into the surface layer of the core-shell structure SBR modified binder can balance the hydrophilic and hydrophobic properties of the binder itself and when it is used in the electrode slurry, which can not only promote and improve the dispersion and suspension stability of particles such as graphite and conductive agent in the aqueous slurry, but also effectively inhibit the floating of the SBR binder, improve the bonding strength and stability between the binder and the foil and graphite, and improve the negative electrode peeling force, thereby ensuring that the active material in the negative electrode sheet is not easy to fall off during repeated expansion and contraction, so that the lithium-ion battery can effectively maintain more stable electrochemical properties.
[0041] In some embodiments of the present application, the inner core layer and the middle shell layer can be formed by polymerization of monomers butadiene and styrene, thereby obtaining a modified binder in which both the inner core and the middle shell layer are made of styrene-butadiene rubber, which has strong cohesion, good heat resistance and chemical corrosion resistance, and a small particle size, many contact points with the active material, strong bonding force, and can maintain its extremely strong bonding properties in the electrolyte for a long time, thereby improving the electrochemical performance of the battery.
[0042] Among them, the mass ratio of butadiene to styrene in the inner core layer is (20-40): (60-80), preferably (20-30): (70-80); the mass ratio of butadiene to styrene in the middle shell layer is (65-75): (25-35), preferably (65-70): (30-35). The core-shell structure SBR modified binder prepared under this condition has a hard core inner layer and a soft shell outer layer structure, and the inner and outer layers have good strength adaptation, which can give the binder extremely strong strength and toughness, improve the distribution position and adhesion strength of the binder in the active material, and play a certain buffering role on the expansion / contraction of the active material particles, thereby inhibiting the expansion of the pole piece, reducing the internal resistance, and improving the cycle performance.
[0043] In some embodiments of the present application, the outer shell layer is formed by grafting unsaturated acid and unsaturated ether substances on the middle shell layer. In this case, the unsaturated acid and unsaturated ether are grafted on the middle shell layer through copolymerization with the SBR molecular chain to form a modified binder.
[0044] In some embodiments of the present application, the unsaturated acid in the shell layer is selected from at least one of acrylic acid, itaconic acid and maleic acid. After the surface of the core-shell structure SBR modified binder is grafted with an unsaturated acid, the binder surface has a hydrophilic group, which is beneficial to improve the dispersion performance between it and other particulate materials in the slurry, and can inhibit the floating of the binder to give full play to its good bonding performance. In order to further improve the structural stability of the modified binder, a combination of two or more unsaturated acids can be used.
[0045] In some embodiments of the present application, the unsaturated ether in the shell layer is selected from at least one of allyl phenyl ether, allyl methyl ether, allyl butyl ether and butyl vinyl ether. After the surface of the core-shell structure SBR modified binder is modified by grafting with a substance having an unsaturated ether bond, its hydrophilic and hydrophobic properties can be balanced, which is conducive to improving the dispersion stability between it and other materials in the slurry, and can inhibit the floating of the binder, and at the same time can further improve the bonding performance between it and other materials, and improve the overall performance of the negative electrode sheet. In order to further improve the structural stability of the modified binder, a combination of two or more unsaturated ethers can be used.
[0046] In the surface grafting modification process of the SBR modified binder with a core-shell structure, the above-mentioned small molecule unsaturated acid and unsaturated ether monomers are selected to be grafted on the surface of the SBR core-shell structure, which not only helps to evenly distribute the binder with the active material and the current collector, improve the energy density and cycle stability of the battery, and improve the coating process on the electrode surface, reducing the problems of coating cracking and coating difficulties; but also enables the binder to retain its good mechanical strength and bonding properties, which helps to maintain the structural integrity of the battery during the cycle process, especially when high-expansion active materials such as silicon are used in the negative electrode, the binder can better resist the stress caused by the volume change of the active material, thereby improving the battery cycle life.
[0047] Furthermore, the unsaturated acid content in the outer shell layer is ≤10wt%. Too high an unsaturated acid content can easily lead to a decrease in the viscoelasticity of the slurry, which is not conducive to resisting the stress changes caused by the volume expansion / contraction of the electrode during the battery cycle, and deteriorates the stability of the electrode structure.
[0048] The content of unsaturated ether in the shell is 1 wt% to 25 wt%, preferably 3 wt% to 20 wt%. If the content of unsaturated ether monomers is too low, the grafting modification effect on the core-shell structure SBR modified binder is not good, and the improvement effect on the dispersion performance and suspension stability of active particulate matter in the slurry is not good; if the content of unsaturated ether monomers is too high, the strength, toughness and thermal stability of the binder itself will be deteriorated, which is not conducive to maintaining the long-term stability and peeling resistance of the electrode structure.
[0049] In order to further improve the dispersibility and bonding performance of the modified binder for active material particles, the mass ratio of unsaturated acid and unsaturated ether in the outer shell layer is set to (4-10): (3-18). The core-shell structure SBR modified binder formed by unsaturated acid and unsaturated ether can significantly improve the compatibility and bonding force of the binder with other materials through the combined modification of its carboxylic acid and ether groups, and at the same time can improve the anti-floating ability of the binder itself, improve the distribution of active material materials in the electrode plate, and improve the overall electrode performance.
[0050] In some embodiments of the present application, the monomer mass ratio of the inner core layer, the middle shell layer and the outer shell layer of the modified binder is (20-65): (20-65): (10-35); preferably (35-60): (20-55): (15-35). By optimizing the monomer ratio of the inner core layer, the middle shell layer and the outer shell layer of the modified binder, the modified binder has excellent cohesion, viscoelasticity and compatibility, significantly improves the problems of electrode coating cracking and material floating during coating, improves the peeling force of the electrode pole piece, and can promote the dispersion of negative electrode active materials and conductive agents, etc., increase the loading amount of active materials, and improve battery energy density and cycle performance.
[0051] The preparation method of the modified binder involved in the embodiment of the present application comprises the following steps: 1) Mix butadiene and styrene, add an initiator to react, and obtain a seed emulsion; 2) adding butadiene and styrene to the seed emulsion and mixing, and adding an initiator to react to obtain a core-shell structured SBR polymer emulsion; 3) adding unsaturated acid and unsaturated ether substances to the core-shell structured SBR polymer emulsion, mixing, and adding an initiator to react, thereby obtaining an aqueous binder emulsion containing the modified binder.
[0052] Wherein, the butadiene and styrene in step 1) are mixed in a certain ratio, for example, a mass ratio of (20-40): (60-80), and a polymerization reaction occurs under the action of an initiator, so as to obtain a core layer structure with high strength. The solvent for the polymerization reaction is a mixed solution of deionized water, an emulsifier, and an electrolyte, so that the polymerization reaction proceeds stably. Among them, emulsifiers such as sodium dodecylbenzene sulfonate, potassium disproportionate rosin acid soap, sodium dodecyl sulfate, fatty acid soap emulsifiers, etc. are not limited in this application; electrolytes such as potassium phosphate, sodium phosphate, etc. are not limited in this application.
[0053] In step 2), butadiene and styrene are mixed in a certain ratio, for example, a mass ratio of (65-75): (25-35), and a polymerization reaction occurs under the action of an initiator, so that a soft middle shell structure with high toughness and high resilience can be obtained, presenting a core-shell structure of the SBR binder. The solvent for the polymerization reaction is the same as that in step 1), and will not be repeated here.
[0054] In step 3), the unsaturated acid and the unsaturated ether are mixed in a certain ratio, for example, a mass ratio of (4-10): (3-18), and grafted into the middle shell layer of the core-shell structure under the action of an initiator, and the hydrophilic functional group with bonding properties is introduced to obtain a core-shell structure SBR binder with high stability, not easy to float and able to stably combine with active material particles. The solvent for the polymerization reaction is a mixed solution of deionized water, an emulsifier, etc., so that the polymerization reaction proceeds stably. The emulsifier is the same as that in step 1), and will not be repeated here.
[0055] The initiator described in the embodiments of the present application may be a redox initiator, such as potassium persulfate, sodium persulfate, diisopropylbenzene peroxide, azobisisobutylonitrile, ferrous sulfate, etc., and the present application does not impose any limitation on this.
[0056] Furthermore, in the preparation process of the modified binder, by adjusting the reaction conditions, such as stability, pressure, reaction time, etc., the production efficiency of the modified binder can be improved while reducing the production cost. Specifically, the preparation method of the modified binder may include the following steps: 1) Deionized water, an emulsifier, and an electrolyte are added to a reaction container, and the mixture is fully stirred and dispersed to serve as a solvent. Then, butadiene and styrene are added into the solvent in a mass ratio of (20-40):(60-80). Under the conditions of a temperature of 3°C to 15°C and a pressure of 3MPa to 15MPa, an initiator is added to promote the reaction of butadiene and styrene. The reaction is carried out for 2h to 5h to obtain a seed emulsion.
[0057] 2) Add emulsifier, deionized water and electrolyte to the seed emulsion, stir and disperse evenly, then put butadiene and styrene into the solvent in a mass ratio of (65-75): (25-35), add initiator to promote the reaction of butadiene and styrene at a temperature of 3°C to 25°C and a pressure of 3MPa to 15MPa, react for 5h to 8h, and obtain a core-shell structured SBR polymer emulsion when the reaction conversion rate reaches 75% to 85%. The structure of the core-shell structured SBR is as follows: ; Here, m and n represent the degree of polymerization of the monomers.
[0058] 3) Add emulsifier and deionized water to the core-shell structured SBR polymer emulsion, stir and disperse evenly, then add unsaturated acid and unsaturated ether into the solvent in a mass ratio of (4-10): (3-18), add initiator and react for 3h-5h at a temperature of 3°C-25°C and a pressure of 1MPa-15MPa, and obtain an aqueous binder emulsion containing the modified binder when the reaction conversion rate reaches 85%-95%. The structure of the modified binder is as follows: ; Wherein, a, b, c, d represent the degree of polymerization of the monomer; -COOX is -COOH or -COOLi, and the lithiation rate of the unsaturated acid such as acrylic acid is ≥90%.
[0059] The solid content of the modified binder contained in the aqueous binder emulsion is 25wt% to 35wt%, the viscosity is 500cps to 1500cps, and the particle size D50 is ≤1μm. It has high bonding performance and a small particle size, can be evenly distributed in the gaps between active material particles, and can be stably combined with active material particles and the surface of the current collector through the carboxyl and ether bonds of its outer shell layer to give full play to the role of the modified binder.
[0060] The modified binder can be used in the electrode plates of lithium-ion batteries to bind the active material particles to the current collector, for example, it can be used in the negative electrode plates.
[0061] The embodiment of the present application also relates to a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active layer formed by coating a negative electrode slurry on the surface of the negative electrode current collector. The negative electrode current collector can be selected from a metal foil or a composite current collector, such as copper foil.
[0062] The negative electrode slurry contains a negative electrode active material and the modified binder or the aqueous binder emulsion prepared by the preparation method.
[0063] The modified binder has extremely strong bonding performance, high strength and high toughness. When used as a modified binder for negative electrode sheets, the amount used can be 1.4wt% to 2wt%; preferably 1.6wt% to 1.8wt%. Compared with conventional SBR modified binders or CMC modified binders, it can achieve high bonding effect with less addition, thereby increasing the loading amount of the main material, i.e., the active substance, and improving the energy density and cycle life of lithium-ion batteries.
[0064] The negative electrode active material in the negative electrode plate can be selected from natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2 or spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy; preferably graphite and silicon-carbon composite. The use of graphite and silicon-carbon composite as negative electrode active materials can effectively improve the energy density of the battery; but at the same time, the volume expansion and contraction rate of silicon materials during charging and discharging is high, which can easily lead to the crushing of the negative electrode structure, the poor contact between the negative electrode active material and the current collector, and thus deteriorate the electrode capacity. Therefore, the addition amount of silicon-carbon composite is preferably 1wt% to 30wt% of the negative electrode sheet; more preferably 5wt% to 16wt%. The proportion of silicon-carbon in the negative electrode system is generally selected to be less than 30wt%, preferably less than 16wt%. Too much silicon-carbon addition will make the expansion deterioration during the battery cell cycle more obvious. Excessive expansion rate of the electrode and battery cell will quickly deteriorate the battery cycle life and even cause safety problems.
[0065] In some embodiments of the present application, the negative electrode plate further includes a conductive agent, which can be selected from one or more of conductive carbon black (SP), acetylene black (ACET), Ketjen black, carbon dots (CDs), carbon nanotubes (CNT), graphene (GPE), carbon nanofibers (CNF), and superconducting carbon, and the present application does not impose any restrictions on this.
[0066] In some embodiments of the present application, the mass ratio of each component in the negative electrode slurry formula can be graphite: silicon carbon: conductive carbon black: carbon nanotubes: CMC: SBR = (65-95): (5-16): (0.1-1): (0.1-1): (0.6-0.8): (1.6-1.8). The solid content of the negative electrode slurry used is 46 wt% to 54 wt%, and the viscosity is 4000 cps to 7000 cps.
[0067] The method for preparing the negative electrode sheet involved in the embodiment of the present application comprises the following steps: I) mixing carboxymethyl cellulose with a conductive agent to obtain a conductive adhesive; II) mixing the conductive glue and the negative electrode active material, and then adding the modified binder to obtain a negative electrode slurry; III) coating the negative electrode slurry on the negative electrode current collector, and drying to obtain the negative electrode sheet as described in the third aspect of the present application.
[0068] The carboxymethyl cellulose described in the above step I) can be a lithium salt or a sodium salt of carboxymethyl cellulose, which is not limited in the present application.
[0069] In the above step II), the conductive glue can be added to the negative electrode active material in steps to make the negative electrode active material dispersed evenly. Specifically, it can be: in a double planetary stirring kettle, add the negative electrode active material such as graphite and silicon-carbon composite, add a certain amount of conductive glue after sufficient stirring, add a certain amount of conductive glue after sufficient wetting and kneading, and after sufficient dispersion, the main material can be evenly dispersed and stably suspended in the slurry, reduce the sedimentation of the main material and avoid the floating of the modified binder, and finally add the modified binder. After sufficient stirring, reverse defoaming can obtain a negative electrode slurry with a solid content of 46wt% to 54wt% and a viscosity of 4000cps to 7000cps. The amount of the conductive glue added for the first time can be adjusted according to the amount of graphite and silicon-carbon composite until it can be fully wetted and bonded to the surface of the main material.
[0070] The lithium-ion battery involved in the embodiment of the present application includes the above-mentioned negative electrode plate or the negative electrode plate made by the above-mentioned method.
[0071] Lithium-ion batteries also include electrolyte, separator and positive electrode. The negative electrode, separator and positive electrode can be stacked in sequence to form a battery cell through a winding process or a lamination process. The battery cell is loaded into the aluminum-plastic film that has been punched and formed, and the battery cell is baked. Then, the electrolyte is injected into the baked and dried battery cell so that the battery cell is immersed in the electrolyte. Then, vacuum packaging, standing, formation and other processes are performed to complete the preparation of the lithium-ion battery.
[0072] The electrolyte, the isolation membrane and the positive electrode plate can be made of any known materials, and this application does not limit this.
[0073] The present application also provides an electrical device or various energy storage systems using batteries as energy storage elements. Electrical devices include but are not limited to mobile phones, tablets, computers, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc.
[0074] In order to make the present invention easier to understand, the present invention will be further described in detail below in conjunction with examples, which are merely illustrative and are not intended to limit the scope of application of the present invention. The raw materials or components used in the present invention can be obtained by commercial routes or conventional methods unless otherwise specified.
[0075] Example 1 1.1 Preparation of modified binder The first step: add deionized water accounting for 50% of the volume of the reactor into the reactor, introduce N2 to replace oxygen, then add sodium dodecylbenzene sulfonate, potassium disproportionate rosin acid soap and electrolyte potassium phosphate, stir well, then put butadiene:styrene in a mass ratio of 30:70 into the deionized water, stir well; under an environment of 5-10°C and a pressure of 5-9Mpa, add initiator ammonium persulfate to initiate the reaction of butadiene and styrene, and obtain a seed emulsion after reacting for 4 hours.
[0076] Step 2: Transfer the above seed emulsion to a large-capacity reactor, add sodium dodecylbenzene sulfonate, potassium disproportionate rosin soap, deionized water, and electrolyte potassium phosphate, then add butadiene:styrene into the seed emulsion in a mass ratio of 65:35, and then add a redox initiator at 15°C and 5 MPa to react for 8 hours. After the reaction conversion rate reaches 85%, a core-shell SBR polymer emulsion is obtained.
[0077] Step 3: On the basis of the above core-shell SBR polymer emulsion, add emulsifier sodium dodecylbenzene sulfonate, disproportionate potassium rosin soap and deionized water, then add acrylic acid and propenyl phenyl ether in a mass ratio of 12:13, add redox initiator at 15°C and 4 MPa pressure for 5 hours, and obtain core-shell SBR modified binder when the conversion rate is 90%. The content of acrylic acid in the outer shell layer is 5wt%, and the content of propenyl phenyl ether is 5.4wt%.
[0078] The ratio of the monomers added in the first step, the second step and the third step is 20:65:15. Figure 1 The solid content of the modified core-shell SBR binder was measured to be 35%, the viscosity was 800 cps, and the particle size D50 was about 350 nm.
[0079] 1.2 Preparation of negative electrode sheets and cells The modified core-shell SBR binder prepared above was stirred into a slurry in a mass ratio of Gr (graphite): SiC (silicon carbon composite): SP (conductive carbon black): CNT (carbon nanotube): CMC: SBR of 90:5:1.2:1.2:0.8:1.8, and then coated, rolled, and slit to prepare a negative electrode sheet. The prepared negative electrode sheet was made into a battery cell test.
[0080] Example 2 The difference from Example 1 is that in the preparation process of the modified binder, the mass ratio of butadiene:styrene in the first step is 20:80, the mass ratio of butadiene:styrene in the second step is 70:30, and in the third step, itaconic acid and allyl methyl ether are added in a mass ratio of 8:4.
[0081] Example 3 The difference from Example 1 is that in the preparation process of the modified binder, the mass ratio of butadiene:styrene in the first step is 25:75, the mass ratio of butadiene:styrene in the second step is 75:35, and in the third step, itaconic acid and butyl vinyl ether are added in a mass ratio of 4:10.
[0082] Example 4 The difference from Example 1 is that, in the preparation process of the modified binder, the mass ratio of monomers butadiene:styrene in the first step is 30:70, the mass ratio of monomers butadiene:styrene in the second step is 70:30, and in the third step, monomers acrylic acid, itaconic acid, propenyl phenyl ether, and allyl butyl ether are added in a mass ratio of 4:6:3:5.
[0083] Example 5 The difference from Example 4 is that during the preparation of the modified binder, the monomers acrylic acid, maleic acid, allyl methyl ether and allyl butyl ether in the third step are added in a mass ratio of 5:5:5:8.
[0084] Example 6 The difference from Example 4 is that, during the preparation of the modified binder, the monomers acrylic acid, maleic acid, itaconic acid, allyl phenyl ether, allyl methyl ether and allyl butyl ether in the third step are added in a mass ratio of 3:3:3:5:5:7.
[0085] Example 7 The difference from Example 6 is that, during the preparation of the modified binder, the ratio of the reactive monomers added in the first step, the second step and the third step is 35:55:10.
[0086] Example 8 The difference from Example 6 is that, during the preparation of the modified binder, the ratio of the reactive monomers added in the first step, the second step and the third step is 60:22:18.
[0087] Example 9 The difference from Example 6 is that, during the preparation of the modified binder, the ratio of the reactive monomers added in the first step, the second step and the third step is 45:20:35.
[0088] Example 10 The difference from Example 9 is that the mass ratio of Gr:SiC:SP:CNT:CMC:SBR is 90:6:0.8:0.8:0.8:1.6.
[0089] Embodiment 11 The difference from Example 10 is that the mass ratio of Gr:SiC:SP:CNT:CMC:SBR is 80:16:0.8:0.8:0.8:1.6.
[0090] Example 12 The difference from Example 10 is that the mass ratio of Gr:SiC:SP:CNT:CMC:SBR is 66:30:0.8:0.8:0.8:1.6.
[0091] Comparative Example 1 1. Preparation of Binder 1.1 The SBR binder was prepared by a conventional emulsion synthesis method of SBR. The specific steps were the same as the first step of preparing the modified binder in Example 1, wherein the ratio of butadiene to styrene in the SBR monomers was 30:70.
[0092] 1.2 A PAA binder was prepared by a conventional emulsion synthesis method for PAA. The specific steps were the same as the first step of preparing the modified binder in Example 1, wherein the monomers of PAA were acrylic acid and acrylonitrile in a ratio of 80:20.
[0093] 2. Preparation of negative electrode sheets and cells The SBR and PAA prepared by the above conventional method were added as binders to the negative electrode slurry formula, and the slurry was made by stirring in a mass ratio of Gr:SiC:SP:CNT:CMC:PAA:SBR of 89.4:5:0.8:0.8:0.5:2.5:1. The slurry was then coated, rolled and slit to obtain electrodes for cell testing.
[0094] Comparative Example 2 The difference from Example 1 is that: In the preparation process of the adhesive, the first step is to react the monomers butadiene and styrene in a mass ratio of 30:70; the second step is to react the monomers butadiene and styrene in a mass ratio of 65:35; the third step is to react the monomers acrylic acid and maleic acid in a mass ratio of 5:5, and then react; During the preparation of the negative electrode sheet, the SBR prepared above was stirred into a slurry according to the ratio of Gr:SiC:SP:CNT:CMC:SBR of 90:5:1:1:0.8:2.2.
[0095] Comparative Example 3 The difference from Example 1 is that: In the preparation process of the adhesive, the first step is to react the monomers butadiene and styrene in a mass ratio of 30:70; the second step is to add the monomers acrylic acid, itaconic acid, propenyl phenyl ether, and allyl methyl ether in a ratio of 4:6:3:5 for reaction; the monomers are added to the inner layer and the outer layer in a mass ratio of 85:15; During the preparation of the negative electrode sheet, the SBR prepared above was stirred into a slurry according to the ratio of Gr:SiC:SP:CNT:CMC:SBR of 90:5:1:1:0.8:2.2.
[0096] Performance Testing 1. Slurry suspension stability test: The negative electrode slurries prepared in the above examples and comparative examples were left to stand for 48 hours and then their solid content and viscosity changes were observed to detect the slurry stability of the negative electrode slurries. The test results are shown in the following table.
[0097] Table 1
[0098] Experimental data analysis: According to Examples 1-10 and Comparative Example 1, it can be found that the slurry made with conventional PAA and SBR has a large viscosity rebound and severe sedimentation, while the slurry made with the core-shell graft modified SBR binder has a low viscosity rebound, excellent performance, no sedimentation, and good slurry fluidity. The more ether and carboxylic acid monomers are added, the better the modification effect is, and the lower the slurry viscosity rebound is.
[0099] 2. Negative electrode appearance test: The prepared slurry was mixed with 130g / m 2 The coating surface density is coated on the 6μm copper foil, and the tape is passed through a 10m coating oven at a speed of 15m / min. The coating temperatures of the 5 coating ovens are set at 85℃, 95℃, 110℃, 115℃, and 95℃ respectively. Then observe the coating appearance of the pole piece. Use winding needles of different diameters to wind pole pieces of different groups, and observe the cracking state of the pole piece under an ultra-depth microscope. The test results are shown in the following table.
[0100] Table 2
[0101] Experimental data analysis: According to the coating and baking comparison of the brittle cracking and flexibility of the pole pieces, it can be seen that the pole pieces made with the core-shell grafted modified SBR binder described in the examples of this application do not crack, and the pole pieces have good flexibility. Comparative Example 1 using conventional PAA and SBR as binders has severe cracking and severe processing deterioration; the SBR binder of Comparative Example 2 has not been ether-modified, and it has slight cracking when using 1mm, 2mm, and 3mm steel needles; the SBR binder of Comparative Example 3 has not been improved in the soft middle layer, and micro-cracks will occur when 1mm, 2mm, and 3mm steel needles are used to wind the pole piece.
[0102] 3. Pole peeling force test; The coated and rolled electrode was cut into 2cm*20cm strips, then attached to a steel plate and stretched at a speed of 5cm / min to test the tensile peeling force of the electrode. The test results are shown in the following table.
[0103] Table 3
[0104] Experimental data analysis: From the test results of the peeling force of the comparative electrode after coating and baking, it can be seen that the peeling force of the electrode prepared by the core-shell grafted modified SBR binder described in the embodiment of the present application is significantly improved compared with that of comparative example 1, and the peeling force is improved more significantly as the type and addition ratio of the outermost modified monomer in the embodiment increase.
[0105] Comparative Example 1 uses conventional PAA and SBR as binders, and its electrode peeling force is very low, which is the worst compared with other groups; the SBR binder of Comparative Example 2 has not been ether-modified, and the peeling force has deteriorated to a certain extent compared with the embodiment; the SBR binder of Comparative Example 3 has not been improved in the soft middle layer, and the peeling force has also deteriorated to a certain extent compared with the embodiment.
[0106] 4. Pole cohesion test after rolling: Similarly, the 2cm*20cm strips cut out were pasted on the steel plate, and then a 1cm wide 3M green tape was pasted on the top of the electrode, and then the green tape was stretched to test the cohesion of the electrode. The test results are shown in the following table.
[0107] Table 4
[0108] Experimental data analysis: The cohesive force test results of the comparative pole pieces after coating and baking show that the cohesive force of the pole piece made by the core-shell graft modified SBR binder described in this embodiment is significantly improved compared with that of comparative example 1, and the cohesive force is improved more significantly as the types and addition ratios of the outermost modified monomers in the embodiment increase. Comparative example 1 uses conventional PAA and SBR as binders, and its pole piece cohesive force is very low, the worst relative to other groups; the SBR binder of comparative example 2 is not ether-modified, and the cohesive force is deteriorated relative to other embodiments; the SBR binder of comparative example 3 is not improved in the soft middle layer, and the cohesive force is also deteriorated relative to the embodiment.
[0109] 5. Internal resistance test of diaphragm after rolling The rolled electrode was cut into small discs with a diameter of 1 cm, and then the internal resistance of the small discs was tested using a diaphragm internal resistance meter ( / mΩ). The test results are shown in the following table.
[0110] Table 5
[0111] Experimental data analysis: The test results of the internal resistance of the electrode after rolling show that the internal resistance of the electrode prepared by the core-shell graft modified SBR binder described in this embodiment is significantly lower than that of the comparative example 1, and the more types and addition ratios of the outermost modified monomers of the binder, the more obvious the reduction of the internal resistance of the membrane. As the amount of silicon carbon added increases, the internal resistance of the membrane will increase slightly.
[0112] When conventional PAA and SBR are used as binders, the internal resistance of the diaphragm is the largest; the internal resistance of the electrode diaphragm corresponding to the SBR binder without ether modification and soft middle layer improvement is also significantly higher than the electrode internal resistance value of the present application. 6. Battery DC internal resistance DCR test The battery cells made of the above-mentioned electrode sheets were sent to measure the battery cell DCR. At 25°C, the discharge rate was 3C for 10s, and the discharge DCR (mΩ) of the battery cells at room temperature was compared. The test results are shown in the following table.
[0113] Table 6
[0114] Experimental data analysis: The comparison of the DCR of the battery cell at room temperature shows that the DCR of the embodiment is significantly reduced compared with the comparative examples 1-3, and the more types and addition ratios of the grafted monomers in the outer layer, the more obvious the DCR reduction. As the amount of silicon carbon added increases, the DCR of the diaphragm will be improved to a certain extent.
[0115] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present application may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. A modified binder, characterized in that: The modified binder comprises an inner core layer, a middle shell layer and an outer shell layer which are sequentially arranged from the inside to the outside; The inner core layer and the middle shell layer are formed of styrene-butadiene rubber, and the strength of the inner core layer is greater than that of the middle shell layer; the outer shell layer is formed by unsaturated acid and unsaturated ether substances.
2. The modified binder according to claim 1, characterized in that: The monomers of the inner core layer and the middle shell layer are butadiene and styrene; Preferably, the mass ratio of butadiene to styrene in the inner core layer is (20-40): (60-80); The mass ratio of butadiene to styrene in the middle shell layer is (65-75):(25-35).
3. The modified binder according to claim 1 or 2, characterized in that: The unsaturated acid is selected from at least one of acrylic acid, itaconic acid and maleic acid; and / or the unsaturated ether is selected from at least one of propenyl phenyl ether, allyl methyl ether, allyl butyl ether and butyl vinyl ether; Preferably, in the shell layer, the content of unsaturated acid is ≤10 wt%; and / or the content of unsaturated ether is 1 wt% to 25 wt%, preferably 3 wt% to 20 wt%; Preferably, in the outer shell layer, the mass ratio of unsaturated acid to unsaturated ether is (4-10):(3-18).
4. The modified binder according to any one of claims 1 to 3, characterized in that: In the modified binder, the monomer mass ratio of the inner core layer, the middle shell layer and the outer shell layer is (20-65): (20-65): (10-35).
5. A method for preparing a modified binder, characterized in that: The following steps are involved: 1) Mix butadiene and styrene, add an initiator to react, and obtain a seed emulsion; 2) adding butadiene and styrene to the seed emulsion and mixing, and adding an initiator to react to obtain a core-shell structured SBR polymer emulsion; 3) adding unsaturated acid and unsaturated ether substances to the core-shell structured SBR polymer emulsion, mixing, and adding an initiator to react, to obtain an aqueous binder emulsion containing the modified binder according to any one of claims 1 to 4.
6. The preparation method according to claim 5, characterized in that: In the aqueous binder emulsion, the solid content of the modified binder is 25wt% to 35wt%, the viscosity is 500cps to 1500cps, and the particle size D50 is ≤1μm.
7. A negative electrode plate, characterized in that: It includes a negative electrode current collector and a negative electrode active layer formed by coating a negative electrode slurry on the surface of the negative electrode current collector; The negative electrode slurry contains a negative electrode active material and a modified binder as described in any one of claims 1 to 4 or an aqueous binder emulsion prepared by the preparation method as described in claim 5 or 6.
8. The negative electrode sheet according to claim 7, characterized in that: The negative electrode active material includes graphite and a silicon-carbon composite; Preferably, the silicon-carbon composite accounts for 1wt% to 30wt% of the negative electrode plate; preferably 5wt% to 16wt%; Preferably, the modified binder accounts for 1.4wt% to 2wt% of the negative electrode sheet; preferably 1.6wt% to 1.8wt%.
9. A method for preparing a negative electrode sheet according to claim 7 or 8, characterized in that: The following steps are involved: I) mixing carboxymethyl cellulose with a conductive agent to obtain a conductive adhesive; II) after mixing the conductive glue and the negative electrode active material, adding the modified binder to obtain the negative electrode slurry; III) coating the negative electrode slurry on the negative electrode current collector and drying to obtain a negative electrode sheet.
10. The preparation method according to claim 9, characterized in that: In the step II), the conductive glue is added to the negative electrode active material step by step to make the negative electrode active material evenly dispersed.
11. A lithium ion battery, comprising the negative electrode sheet as claimed in claim 7 or 8, or the negative electrode sheet prepared by the preparation method as claimed in claim 9 or 10.
Citation Information
Cited By
Negative electrode binder, electrode plate and battery
CN121343519A
Negative electrode binder, preparation method of negative electrode binder, negative electrode plate and battery
CN121687954A
